A mother's wisdom, a leader's charge: Her Royal Highness's inspiring call to IIUM graduates - Rahman, Shukran Abdul (Human Assistance & Development International Inc. (HADI Inc.), 2025)
In universities around the world, the Charge to the Graduates is a distinguished tradition in which the institution's highest authority delivers a final message of wisdom, aspiration, and moral direction to the degree recipients. More than a ceremonial speech, the Charge is a moment when the university's core values are articulated clearly and personally, reminding graduates of the noble responsibilities that accompany their academic achievements. Through this Charge, the Constitutional Head, Chancellor, or Rector conveys the institution's hopes, expectations, and guiding moral values as graduates transition from students into bearers of the university's mission. In the context of the International Islamic University Malaysia (IIUM), which conducted her 41st Convocation recently, the Charge carries even deeper significance. Rooted in a philosophy that integrates revelation, reason, and compassion, the Charge becomes a moral mandate, calling graduates to embody Tawhid, uphold justice, and serve humanity. It is both an honor and an amanah that connects each graduating cohort to the soul and identity of the university.